Sistem Pendukung Keputusan Menentukan Keluarga Miskin Dalam Rangka Mendapatkan Bantuan Dana PKH - Resy Anggun Sari; Mei ratnasari (Cerdika: Jurnal Ilmiah Indonesia, 2021)
The Hope Family Program is a program that provides conditional cash transfers to Very Poor Households which have been designated as PKH participants with certain conditions. so far more programs or policies have failed to be implemented than those that have been successfully implemented, the Government Program in tackling the economic crisis that has occurred so far is by providing direct assistance to very poor families in every village throughout Indonesia. Limau Subdistrict still experiences some obstacles and problems in determining the recipients of some assistance that has been given by the central government, one of which is the Family Hope Program (PKH). Namely, the instrument must conduct a direct survey in determining who is eligible or does not get help in accordance with data that has been provided by the Social Service. The data recorded still uses paper that is very prone to be lost, wet, or even burned. Therefore we need a system or application that makes it easy to determine who the recipients of the family hope program are. As well as making stored and archived reports safely to facilitate the determination of PKH beneficiaries. The method used to determine the acceptance of PKH rocks is the Topsis Method.